Managing Postpartum Discomfort with Non-pharmacological Pain Management (Cold Compresses) in Postpartum Mothers at Salatiga Regional Hospital - Umniyatul Ulaya; Ana Puji Astuti (International Forum of Researchers and Lecturers, 2026)
The postpartum period is the six-week recovery period for the uterine organs after childbirth. A common phenomenon is discomfort due to perineal rupture, experienced by approximately 83% of women giving birth in Indonesia. Perineal pain can hinder early mobilization, disrupt rest patterns, and impede mother-infant interaction. Data from Salatiga Regional Hospital (2024-2025) recorded 634 cases of spontaneous labor with perineal wound pain. This scientific paper aims to describe the management of postpartum discomfort using non-pharmacological pain management (cold compresses). The researchers used a descriptive case study method to address the nursing problem of postpartum discomfort. The case subjects were women who spontaneously underwent postpartum labor experiencing perineal wound pain. The chosen intervention was cold compress, a form of skin stimulation is using low temperatures to produce analgesic effects, reduce edema, and stimulate endorphin release. Implementation was carried out for three days to reduce pain levels as measured by the Numeric Rating Scale (NRS). Previous research has shown that cold compress therapy can significantly reduce pain intensity from moderate (scale 4) to no pain (scale 0). Cold compresses were more effective in reducing pain than the control group that did not receive cold compresses. It is recommended that the public, especially postpartum mothers, independently apply cold compresses as an inexpensive and easy method to reduce perineal pain. Healthcare institutions are expected to use the results of this study as a source of information to improve the quality of maternity nursing services through non-pharmacological methods that are safe for both mother and baby.